Preparation method of high-basicity polyaluminum chloride
By using raw materials such as hydrochloric acid and aluminum hydroxide in the preparation of polyaluminum chloride, and combining chitosan to blend kaolin liquid and hydroxyapatite agent, the existing high-salt-based polyaluminum chloride purification efficiency and stability problems are solved. , achieving more efficient removal rate and better durability.
Patent Information
- Application Number
- CN202411608905.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing high-salt-based polyaluminum chloride has poor purification efficiency, making it difficult to balance COD, turbidity and heavy metal removal rates, and the durability and stability of the product is also poor.
Hydrochloric acid and aluminum hydroxide are used as raw materials, combined with calcium aluminate powder and calcium carbonate powder, and after spray drying, chitosan is added to blend kaolin liquid and hydroxyapatite agent. By coordinating the coordination between the raw materials, it is prepared. High salt-based polyaluminum chloride.
The balance improvements in COD, turbidity and heavy metal removal rate of high-salt-based polyaluminum chloride are significantly improved, while improving the durability and stability of the product.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyaluminium chloride, and in particular to a method for preparing high-basicity polyaluminium chloride. Background Art
[0002] Polyaluminium chloride is an inorganic substance, an emerging water purification material and an inorganic polymer coagulant. Polyaluminium chloride has the advantages of good spray drying stability, wide adaptability to water areas, fast hydrolysis rate, strong adsorption capacity, large alum flocs, fast dense precipitation, low effluent turbidity and good dehydration performance. However, it has poor stability and is corrosive, so it needs to be sealed and stored before use.
[0003] The existing high-basicity polyaluminium chloride has poor purification efficiency, and it is difficult to improve the COD, turbidity and heavy metal removal rates in a balanced manner. At the same time, the product has poor durability and stability, and the removal rate decreases significantly after repeated use, which limits the efficiency of the product. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide a method for preparing high basicity polyaluminium chloride to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a method for preparing high basicity polyaluminium chloride, comprising the following steps: Step 1: 30% hydrochloric acid and aluminum hydroxide are used as raw materials, reacted at 100°C for 120 minutes, then cooled to 65°C, calcium aluminate powder is added thereto, and the reaction is continued at 100°C for 50 minutes; Step 2: Then add calcium carbonate powder, continue to react for 30 minutes, control the pH value to 4, and then spray dry to obtain solid polyaluminium chloride; Step 3: Add solid polyaluminium chloride to chitosan-kaolin solution which is 2-5 times the total amount of solid polyaluminium chloride, and then add hydroxyapatite which is 10-15% of the total amount of solid polyaluminium chloride, stir thoroughly, filter and dry to obtain high basicity polyaluminium chloride.
[0006] Preferably, the mass ratio of hydrochloric acid, aluminum hydroxide, calcium aluminate powder and calcium carbonate powder is (5-8):2:(3-5):2.
[0007] Preferably, the preparation method of the chitosan-kaolin solution is: S01: Heat treat kaolin at 130-140℃ for 10-15min, then heat to 220℃ at a rate of 2-5℃ / min, keep warm for 5min, and then air cool to room temperature; S02: Preparation of modified solution: S021: Stir and mix the silicon carbide whiskers in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry; irradiate the dried silicon carbide whiskers in a proton irradiation box for 10-15 minutes at an irradiation power of 350-400W, and obtain irradiated silicon carbide whiskers after the irradiation is completed; S022: 5-8 parts of irradiated silicon carbide whiskers, 1-3 parts of nano-silica sol, 5-8 parts of sodium lignin sulfonate solution, and 2-4 parts of lanthanum chloride solution are stirred to obtain a modified solution; S03: 3-5 parts of kaolin in S01 and 4-7 parts of modified liquid are mixed and ball-milled at a speed of 1000 r / min for 2 h to obtain a modified kaolin liquid; S04: The modified kaolin liquid and the chitosan blending agent are stirred in a weight ratio of 2:5 to obtain a chitosan-blended kaolin liquid.
[0008] Preferably, the mass fraction of the sodium lignin sulfonate solution is 2-5%; the mass fraction of the lanthanum chloride solution is 3-6%.
[0009] Preferably, the chitosan conditioning agent is prepared by mixing chitosan solution, nano-silicon dioxide and silane coupling agent in a weight ratio of 4:3:1.
[0010] Preferably, the mass fraction of the chitosan solution is 2-5%; and the silane coupling agent is silane coupling agent KH560.
[0011] Preferably, the preparation method of the hydroxyapatite agent is: S11: immersing the hydroxyapatite in a 5% sodium silicate solution having a mass fraction of 3-5 times the total amount of the hydroxyapatite and stirring sufficiently to obtain a hydroxyapatite liquid; S12: immersing the nano-titanium dioxide into a sufficient amount of yttrium nitrate solution until fully immersed, filtering and drying after the immersion is completed, to obtain a nano-titanium dioxide agent; S13: 5-8 parts of hydroxyapatite liquid, 2-4 parts of sodium dodecylbenzene sulfonate and 3-5 parts of nano titanium dioxide agent are mixed and ball-milled. After the ball-milling is completed, the mixture is filtered and dried to obtain the hydroxyapatite agent.
[0012] Preferably, the mass fraction of the yttrium nitrate solution is 2-5%.
[0013] Preferably, the blending process is performed at a ball milling speed of 1000 r / min and the ball milling is performed for 2 hours.
[0014] Preferably, the immersion power for full immersion is 350-400W, and the immersion time is 20-30min.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The high-basicity polyaluminium chloride of the invention adopts hydrochloric acid and aluminium hydroxide as raw materials, and is prepared into solid polyaluminium chloride in combination with calcium carbonate powder and calcium aluminate powder. Then, chitosan is used to adjust kaolin liquid and hydroxyapatite agent for coordination and synergy. Through the coordination and synergy between the raw materials, the COD, turbidity and heavy metal removal rate of the obtained high-basicity polyaluminium chloride product are balanced and improved, and the product durability and stability effect is remarkable. Chitosan is used to adjust kaolin liquid. Kaolin is firstly heat-treated at 130-140°C for 10-15min, then heated to 220°C at a rate of 2-5°C / min, kept warm for 5min, and then air-cooled to room temperature. After heat treatment, the obtained high-basicity polyaluminium chloride product is improved in COD, turbidity and heavy metal removal rate. , optimize the active efficiency and active stability of kaolin, and the silicon carbide whiskers are irradiated and then combined with potassium permanganate solution to facilitate better coordination of kaolin in nano-silica sol, sodium lignin sulfonate solution and lanthanum chloride solution. The modified liquid obtained can better improve kaolin, and then be coordinated and improved with chitosan blending agent, which can further optimize the coordination between the raw materials of the system. The hydroxyapatite agent is combined with sodium silicate solution and then coordinated with nano-titanium dioxide agent, so that the hydroxyapatite agent and chitosan-blended kaolin liquid have better coordination effect, and the performance of the product is further improved. DETAILED DESCRIPTION
[0016] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] A method for preparing high basicity polyaluminium chloride of the present embodiment comprises the following steps: Step 1: 30% hydrochloric acid and aluminum hydroxide are used as raw materials, reacted at 100°C for 120 minutes, then cooled to 65°C, calcium aluminate powder is added thereto, and the reaction is continued at 100°C for 50 minutes; Step 2: Then add calcium carbonate powder, continue to react for 30 minutes, control the pH value to 4, and then spray dry to obtain solid polyaluminium chloride; Step 3: Add solid polyaluminium chloride to chitosan-kaolin solution which is 2-5 times the total amount of solid polyaluminium chloride, and then add hydroxyapatite which is 10-15% of the total amount of solid polyaluminium chloride, stir thoroughly, filter and dry to obtain high basicity polyaluminium chloride.
[0018] The mass ratio of hydrochloric acid, aluminum hydroxide, calcium aluminate powder and calcium carbonate powder in this embodiment is (5-8):2:(3-5):2.
[0019] The preparation method of chitosan-mixed kaolin solution of the present embodiment is as follows: S01: Heat treat kaolin at 130-140℃ for 10-15min, then heat to 220℃ at a rate of 2-5℃ / min, keep warm for 5min, and then air cool to room temperature; S02: Preparation of modified solution: S021: Stir and mix the silicon carbide whiskers in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry; irradiate the dried silicon carbide whiskers in a proton irradiation box for 10-15 minutes at an irradiation power of 350-400W, and obtain irradiated silicon carbide whiskers after the irradiation is completed; S022: 5-8 parts of irradiated silicon carbide whiskers, 1-3 parts of nano-silica sol, 5-8 parts of sodium lignin sulfonate solution, and 2-4 parts of lanthanum chloride solution are stirred to obtain a modified solution; S03: 3-5 parts of kaolin in S01 and 4-7 parts of modified liquid are mixed and ball-milled at a speed of 1000 r / min for 2 h to obtain a modified kaolin liquid; S04: The modified kaolin liquid and the chitosan blending agent are stirred in a weight ratio of 2:5 to obtain a chitosan-blended kaolin liquid.
[0020] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2-5%; the mass fraction of the lanthanum chloride solution is 3-6%.
[0021] The chitosan conditioning agent of this embodiment is prepared by mixing chitosan solution, nano silicon dioxide and silane coupling agent in a weight ratio of 4:3:1.
[0022] The mass fraction of the chitosan solution in this embodiment is 2-5%; the silane coupling agent is silane coupling agent KH560.
[0023] The preparation method of the hydroxyapatite agent of this embodiment is: S11: immersing the hydroxyapatite in a 5% sodium silicate solution having a mass fraction of 3-5 times the total amount of the hydroxyapatite and stirring sufficiently to obtain a hydroxyapatite liquid; S12: immersing the nano-titanium dioxide into a sufficient amount of yttrium nitrate solution until fully immersed, filtering and drying after the immersion is completed, to obtain a nano-titanium dioxide agent; S13: 5-8 parts of hydroxyapatite liquid, 2-4 parts of sodium dodecylbenzene sulfonate and 3-5 parts of nano titanium dioxide agent are mixed and ball-milled. After the ball-milling is completed, the mixture is filtered and dried to obtain the hydroxyapatite agent.
[0024] The mass fraction of the yttrium nitrate solution in this embodiment is 2-5%.
[0025] The ball milling speed of the blended ball milling treatment in this embodiment is 1000 r / min, and the ball milling is performed for 2 h.
[0026] The immersion power for full immersion in this embodiment is 350-400W, and the immersion time is 20-30min.
[0027] Example 1. A method for preparing high basicity polyaluminium chloride of the present embodiment comprises the following steps: Step 1: 30% hydrochloric acid and aluminum hydroxide are used as raw materials, reacted at 100°C for 120 minutes, then cooled to 65°C, calcium aluminate powder is added thereto, and the reaction is continued at 100°C for 50 minutes; Step 2: Then add calcium carbonate powder, continue to react for 30 minutes, control the pH value to 4, and then spray dry to obtain solid polyaluminium chloride; Step 3: Add solid polyaluminium chloride to chitosan-kaolin solution which is twice the total amount of solid polyaluminium chloride, and then add hydroxyapatite which is 10% of the total amount of solid polyaluminium chloride, stir thoroughly, filter and dry to obtain high basicity polyaluminium chloride.
[0028] The mass ratio of hydrochloric acid, aluminum hydroxide, calcium aluminate powder and calcium carbonate powder in this embodiment is 5:2:3:2.
[0029] The preparation method of chitosan-mixed kaolin solution of the present embodiment is as follows: S01: Heat-treat kaolin at 130°C for 10 min, then heat to 220°C at a rate of 2°C / min, keep warm for 5 min, and then air-cool to room temperature; S02: Preparation of modified solution: S021: Stir and mix the silicon carbide whiskers in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry; irradiate the dried silicon carbide whiskers in a proton irradiation box for 10 minutes at an irradiation power of 350W, and obtain irradiated silicon carbide whiskers after the irradiation is completed; S022: 5 parts of irradiated silicon carbide whiskers, 1 part of nano-silica sol, 5 parts of sodium lignin sulfonate solution, and 2 parts of lanthanum chloride solution are stirred to obtain a modified solution; S03: 3 parts of kaolin in S01 and 4 parts of modified liquid were mixed and ball-milled at a speed of 1000 r / min for 2 h to obtain modified kaolin liquid; S04: The modified kaolin liquid and the chitosan blending agent are stirred in a weight ratio of 2:5 to obtain a chitosan-blended kaolin liquid.
[0030] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2%; the mass fraction of the lanthanum chloride solution is 3%.
[0031] The chitosan conditioning agent of this embodiment is prepared by mixing chitosan solution, nano silicon dioxide and silane coupling agent in a weight ratio of 4:3:1.
[0032] The mass fraction of the chitosan solution in this embodiment is 2%; the silane coupling agent is silane coupling agent KH560.
[0033] The preparation method of the hydroxyapatite agent of this embodiment is: S11: immersing the hydroxyapatite in a 5% sodium silicate solution having a mass fraction of 3 times the total amount of the hydroxyapatite and stirring sufficiently to obtain a hydroxyapatite liquid; S12: immersing the nano-titanium dioxide into a sufficient amount of yttrium nitrate solution until fully immersed, filtering and drying after the immersion is completed, to obtain a nano-titanium dioxide agent; S13: 5 parts of hydroxyapatite liquid, 2 parts of sodium dodecylbenzene sulfonate and 3 parts of nano titanium dioxide are mixed and ball-milled. After the ball-milling is completed, the mixture is filtered and dried to obtain a hydroxyapatite agent.
[0034] The mass fraction of the yttrium nitrate solution in this embodiment is 2%.
[0035] The ball milling speed of the blended ball milling treatment in this embodiment is 1000 r / min, and the ball milling is performed for 2 h.
[0036] The immersion power for full immersion in this embodiment is 350 W, and the immersion time is 20 min.
[0037] Example 2. A method for preparing high basicity polyaluminium chloride of the present embodiment comprises the following steps: Step 1: 30% hydrochloric acid and aluminum hydroxide are used as raw materials, reacted at 100°C for 120 minutes, then cooled to 65°C, calcium aluminate powder is added thereto, and the reaction is continued at 100°C for 50 minutes; Step 2: Then add calcium carbonate powder, continue to react for 30 minutes, control the pH value to 4, and then spray dry to obtain solid polyaluminium chloride; Step 3: Add solid polyaluminium chloride to chitosan-kaolin solution which is 5 times the total amount of solid polyaluminium chloride, and then add hydroxyapatite which is 15% of the total amount of solid polyaluminium chloride, stir thoroughly, filter and dry to obtain high basicity polyaluminium chloride.
[0038] The mass ratio of hydrochloric acid, aluminum hydroxide, calcium aluminate powder and calcium carbonate powder in this embodiment is 8:2:5:2.
[0039] The preparation method of chitosan-mixed kaolin solution of the present embodiment is as follows: S01: Heat-treat kaolin at 140°C for 15 min, then heat to 220°C at a rate of 5°C / min, keep warm for 5 min, and then air-cool to room temperature; S02: Preparation of modified solution: S021: Stir and mix the silicon carbide whiskers in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry; irradiate the dried silicon carbide whiskers in a proton irradiation box for 15 minutes at an irradiation power of 400 W, and obtain irradiated silicon carbide whiskers after the irradiation is completed; S022: 8 parts of irradiated silicon carbide whiskers, 3 parts of nano-silica sol, 8 parts of sodium lignin sulfonate solution, and 4 parts of lanthanum chloride solution are stirred to obtain a modified solution; S03: 5 parts of kaolin in S01 and 7 parts of modified liquid were mixed and ball-milled at a speed of 1000 r / min for 2 h to obtain modified kaolin liquid; S04: The modified kaolin liquid and the chitosan blending agent are stirred in a weight ratio of 2:5 to obtain a chitosan-blended kaolin liquid.
[0040] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5%; the mass fraction of the lanthanum chloride solution is 6%.
[0041] The chitosan conditioning agent of this embodiment is prepared by mixing chitosan solution, nano silicon dioxide and silane coupling agent in a weight ratio of 4:3:1.
[0042] The mass fraction of the chitosan solution in this embodiment is 5%; the silane coupling agent is silane coupling agent KH560.
[0043] The preparation method of the hydroxyapatite agent of this embodiment is: S11: immersing the hydroxyapatite in a 5% sodium silicate solution with a mass fraction of 5 times the total amount of the hydroxyapatite and stirring sufficiently to obtain a hydroxyapatite liquid; S12: immersing the nano-titanium dioxide into a sufficient amount of yttrium nitrate solution until fully immersed, filtering and drying after the immersion is completed, to obtain a nano-titanium dioxide agent; S13: 8 parts of hydroxyapatite liquid, 4 parts of sodium dodecylbenzene sulfonate and 5 parts of nano titanium dioxide are mixed and ball-milled. After the ball-milling is completed, the mixture is filtered and dried to obtain a hydroxyapatite agent.
[0044] The mass fraction of the yttrium nitrate solution in this embodiment is 5%.
[0045] The ball milling speed of the blended ball milling treatment in this embodiment is 1000 r / min, and the ball milling is performed for 2 h.
[0046] The immersion power for full immersion in this embodiment is 400 W, and the immersion time is 30 min.
[0047] Example 3. A method for preparing high basicity polyaluminium chloride of the present embodiment comprises the following steps: Step 1: 30% hydrochloric acid and aluminum hydroxide are used as raw materials, reacted at 100°C for 120 minutes, then cooled to 65°C, calcium aluminate powder is added thereto, and the reaction is continued at 100°C for 50 minutes; Step 2: Then add calcium carbonate powder, continue to react for 30 minutes, control the pH value to 4, and then spray dry to obtain solid polyaluminium chloride; Step 3: Add solid polyaluminium chloride to chitosan-kaolin solution which is 3.5 times the total amount of solid polyaluminium chloride, and then add hydroxyapatite which is 12.5% of the total amount of solid polyaluminium chloride, stir thoroughly, filter and dry to obtain high basicity polyaluminium chloride.
[0048] The mass ratio of hydrochloric acid, aluminum hydroxide, calcium aluminate powder and calcium carbonate powder in this embodiment is 6.5:2:4:2.
[0049] The preparation method of chitosan-mixed kaolin solution of the present embodiment is as follows: S01: Heat treat kaolin at 135°C for 12.5 min, then heat to 220°C at a rate of 3.5°C / min, keep warm for 5 min, and then air cool to room temperature; S02: Preparation of modified solution: S021: Stir and mix the silicon carbide whiskers in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry; irradiate the dried silicon carbide whiskers in a proton irradiation box for 12.5 minutes at an irradiation power of 370W, and obtain irradiated silicon carbide whiskers after the irradiation is completed; S022: 6.5 parts of irradiated silicon carbide whiskers, 2 parts of nano-silica sol, 6.5 parts of sodium lignin sulfonate solution, and 3 parts of lanthanum chloride solution are stirred to obtain a modified solution; S03: 4 parts of kaolin from S01 and 5.5 parts of modified liquid were mixed and ball-milled at a speed of 1000 r / min for 2 h to obtain modified kaolin liquid; S04: The modified kaolin liquid and the chitosan blending agent are stirred in a weight ratio of 2:5 to obtain a chitosan-blended kaolin liquid.
[0050] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 3.5%; the mass fraction of the lanthanum chloride solution is 4.5%.
[0051] The chitosan conditioning agent of this embodiment is prepared by mixing chitosan solution, nano silicon dioxide and silane coupling agent in a weight ratio of 4:3:1.
[0052] The mass fraction of the chitosan solution in this embodiment is 3.5%; the silane coupling agent is silane coupling agent KH560.
[0053] The preparation method of the hydroxyapatite agent of this embodiment is: S11: immersing the hydroxyapatite in a 5% sodium silicate solution having a mass fraction of 4 times the total amount of the hydroxyapatite and stirring sufficiently to obtain a hydroxyapatite liquid; S12: immersing the nano-titanium dioxide into a sufficient amount of yttrium nitrate solution until fully immersed, filtering and drying after the immersion is completed, to obtain a nano-titanium dioxide agent; S13: 6.5 parts of hydroxyapatite liquid, 3 parts of sodium dodecylbenzene sulfonate and 4 parts of nano titanium dioxide agent are mixed and ball-milled. After the ball-milling is completed, the mixture is filtered and dried to obtain a hydroxyapatite agent.
[0054] The mass fraction of the yttrium nitrate solution in this embodiment is 3.5%.
[0055] The ball milling speed of the blended ball milling treatment in this embodiment is 1000 r / min, and the ball milling is performed for 2 h.
[0056] The immersion power for full immersion in this embodiment is 370W, and the immersion time is 25 minutes.
[0057] Example 4. A method for preparing high basicity polyaluminium chloride of the present embodiment comprises the following steps: Step 1: 30% hydrochloric acid and aluminum hydroxide are used as raw materials, reacted at 100°C for 120 minutes, then cooled to 65°C, calcium aluminate powder is added thereto, and the reaction is continued at 100°C for 50 minutes; Step 2: Then add calcium carbonate powder, continue to react for 30 minutes, control the pH value to 4, and then spray dry to obtain solid polyaluminium chloride; Step 3: Add solid polyaluminium chloride to chitosan-kaolin solution which is 2-5 times the total amount of solid polyaluminium chloride, and then add hydroxyapatite which is 10-15% of the total amount of solid polyaluminium chloride, stir thoroughly, filter and dry to obtain high basicity polyaluminium chloride.
[0058] The mass ratio of hydrochloric acid, aluminum hydroxide, calcium aluminate powder and calcium carbonate powder in this embodiment is 5.5:2:3.5:2.
[0059] The preparation method of chitosan-mixed kaolin solution of the present embodiment is as follows: S01: Heat-treat kaolin at 132°C for 12 min, then heat to 220°C at a rate of 3°C / min, keep warm for 5 min, and then air-cool to room temperature; S02: Preparation of modified solution: S021: Stir and mix the silicon carbide whiskers in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry; irradiate the dried silicon carbide whiskers in a proton irradiation box for 12 minutes at an irradiation power of 360W, and obtain irradiated silicon carbide whiskers after the irradiation is completed; S022: 6 parts of irradiated silicon carbide whiskers, 2 parts of nano-silica sol, 6 parts of sodium lignin sulfonate solution, and 3 parts of lanthanum chloride solution are stirred to obtain a modified solution; S03: 4 parts of kaolin in S01 and 5 parts of modified liquid were mixed and ball-milled at a speed of 1000 r / min for 2 h to obtain modified kaolin liquid; S04: The modified kaolin liquid and the chitosan blending agent are stirred in a weight ratio of 2:5 to obtain a chitosan-blended kaolin liquid.
[0060] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 3%; the mass fraction of the lanthanum chloride solution is 4%.
[0061] The chitosan conditioning agent of this embodiment is prepared by mixing chitosan solution, nano silicon dioxide and silane coupling agent in a weight ratio of 4:3:1.
[0062] The mass fraction of the chitosan solution in this embodiment is 3%; the silane coupling agent is silane coupling agent KH560.
[0063] The preparation method of the hydroxyapatite agent of this embodiment is: S11: immersing the hydroxyapatite in a 5% sodium silicate solution having a mass fraction of 4 times the total amount of the hydroxyapatite and stirring sufficiently to obtain a hydroxyapatite liquid; S12: immersing the nano-titanium dioxide into a sufficient amount of yttrium nitrate solution until fully immersed, filtering and drying after the immersion is completed, to obtain a nano-titanium dioxide agent; S13: 6 parts of hydroxyapatite liquid, 3 parts of sodium dodecylbenzene sulfonate and 4 parts of nano titanium dioxide agent are mixed and ball-milled. After the ball-milling is completed, the mixture is filtered and dried to obtain a hydroxyapatite agent.
[0064] The mass fraction of the yttrium nitrate solution in this embodiment is 3%.
[0065] The ball milling speed of the blended ball milling treatment in this embodiment is 1000 r / min, and the ball milling is performed for 2 h.
[0066] The immersion power for full immersion in this embodiment is 360 W, and the immersion time is 22 minutes.
[0067] Comparative Example 1. The difference from Example 3 is that no chitosan is added to the kaolin solution.
[0068] Comparative Example 2. The difference from Example 3 is that no modifying liquid is added in the preparation of the chitosan-kaolin solution.
[0069] Comparative Example 3. The difference from Example 3 is that no irradiated silicon carbide whiskers are added to the modified solution.
[0070] Comparative Example 4. The difference from Example 3 is that the chitosan conditioning agent is replaced by water.
[0071] Comparative Example 5. The difference from Example 3 is that no hydroxyapatite agent is added.
[0072] Comparative Example 6. The difference from Example 3 is that no nano titanium dioxide agent is added to the hydroxyapatite agent.
[0073] Comparative Example 7. The difference from Example 3 is that no hydroxyapatite liquid is added to the hydroxyapatite agent.
[0074] The product performance tests of Examples 1-4 and Comparative Examples 1-7 are as follows: It can be seen from Comparative Examples 1-7 and Example 3 that the product of Example 3 has excellent COD removal rate, heavy metal Cr removal rate and turbidity removal rate. At the same time, after the product is used 10 times, the performance stability of the product is remarkable. The present invention does not add chitosan to adjust kaolin liquid or does not add hydroxyapatite agent, and the performance of the product has a significant deterioration trend. The synergistic effect of the two is used to achieve the most significant product performance effect. When no modifying liquid is added in the preparation of chitosan-blended kaolin liquid, no irradiated silicon carbide whiskers are added to the modifying liquid, water is used to replace the chitosan blending agent, nano titanium dioxide agent is not added to the hydroxyapatite agent, and hydroxyapatite liquid is not added to the hydroxyapatite agent, the performance of the products tends to deteriorate. Only the chitosan-blended kaolin liquid obtained by combining the modifying liquid obtained by the method of the present invention with the specific raw materials of the present invention, and the hydroxyapatite agent obtained by the method of the present invention, have the most significant product performance effects. The effects of other methods are not as obvious as those of the present invention.
[0075] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0076] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing high basicity polyaluminium chloride, characterized in that: The following steps are involved: Step 1: 30% hydrochloric acid and aluminum hydroxide are used as raw materials, reacted at 100°C for 120 minutes, then cooled to 65°C, calcium aluminate powder is added thereto, and the reaction is continued at 100°C for 50 minutes; Step 2: Then add calcium carbonate powder, continue to react for 30 minutes, control the pH value to 4, and then spray dry to obtain solid polyaluminium chloride; Step 3: Add solid polyaluminium chloride to chitosan-kaolin solution which is 2-5 times the total amount of solid polyaluminium chloride, and then add hydroxyapatite which is 10-15% of the total amount of solid polyaluminium chloride, stir thoroughly, filter and dry to obtain high basicity polyaluminium chloride.
2. The method for preparing a high basicity polyaluminium chloride according to claim 1, characterized in that: The mass ratio of hydrochloric acid, aluminum hydroxide, calcium aluminate powder and calcium carbonate powder is (5-8):2: (3-5):
2.
3. The method for preparing a high basicity polyaluminium chloride according to claim 1, characterized in that: The preparation method of the chitosan-kaolin solution is as follows: S01: Heat treat kaolin at 130-140℃ for 10-15min, then heat to 220℃ at a rate of 2-5℃ / min, keep warm for 5min, and then air cool to room temperature; S02: Preparation of modified solution: S021: Stir and mix the silicon carbide whiskers in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry; irradiate the dried silicon carbide whiskers in a proton irradiation box for 10-15 minutes at an irradiation power of 350-400W, and obtain irradiated silicon carbide whiskers after the irradiation is completed; S022: 5-8 parts of irradiated silicon carbide whiskers, 1-3 parts of nano-silica sol, 5-8 parts of sodium lignin sulfonate solution, and 2-4 parts of lanthanum chloride solution are stirred to obtain a modified solution; S03: 3-5 parts of kaolin in S01 and 4-7 parts of modified liquid are mixed and ball-milled at a speed of 1000 r / min for 2 h to obtain a modified kaolin liquid; S04: The modified kaolin liquid and the chitosan blending agent are stirred in a weight ratio of 2:5 to obtain a chitosan-blended kaolin liquid.
4. The method for preparing high basicity polyaluminium chloride according to claim 3, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 2-5%; the mass fraction of the lanthanum chloride solution is 3-6%.
5. The method for preparing high basicity polyaluminium chloride according to claim 3, characterized in that: The chitosan conditioning agent is prepared by mixing chitosan solution, nano silicon dioxide and silane coupling agent in a weight ratio of 4:3:
1.
6. The method for preparing high basicity polyaluminium chloride according to claim 5, characterized in that: The mass fraction of the chitosan solution is 2-5%; the silane coupling agent is silane coupling agent KH560.
7. The method for preparing high basicity polyaluminium chloride according to claim 1, characterized in that: The preparation method of the hydroxyapatite agent is: S11: immersing the hydroxyapatite in a 5% sodium silicate solution having a mass fraction of 3-5 times the total amount of the hydroxyapatite and stirring sufficiently to obtain a hydroxyapatite liquid; S12: immersing the nano-titanium dioxide into a sufficient amount of yttrium nitrate solution until fully immersed, filtering and drying after the immersion is completed, to obtain a nano-titanium dioxide agent; S13: 5-8 parts of hydroxyapatite liquid, 2-4 parts of sodium dodecylbenzene sulfonate and 3-5 parts of nano titanium dioxide agent are mixed and ball-milled. After the ball-milling is completed, the mixture is filtered and dried to obtain the hydroxyapatite agent.
8. The method for preparing high basicity polyaluminium chloride according to claim 7, characterized in that: The mass fraction of the yttrium nitrate solution is 2-5%.
9. The method for preparing high basicity polyaluminium chloride according to claim 7, characterized in that: The ball milling speed of the blended product was 1000 r / min, and the ball milling lasted for 2 h.
10. The method for preparing high basicity polyaluminium chloride according to claim 7, characterized in that: The immersion power for full immersion is 350-400W, and the immersion time is 20-30min.
Citation Information
Cited By
Special aluminum alloy power cable for railway and preparation method thereof
CN120137491A
Flocculating agent suitable for high-concentration sludge and preparation method thereof
CN120698681A